Moderating Effect Of Institutional Environment On The Ownership Structure And Capital Structure Relationship Of Chinese Listed Companies - Wang, Chu (2023)
This study aims to analyze the impact of companies' ownership structure on corporate capital structure, moderated by labor and product market maturity from the perspectives of resource-based and contingency views.